(untitled) (Jurnal Bahasa, 2019)
The lexical selection in song lyrics requires a serious thought from the author because the lyrics should be poetic, while the desired message is to be accurately communicated to the listeners. The purpose of this study is to describe the meaning and the mind of the author through the figurative language used in the song "Mati Hidup Semula". Two implicit expressions have been selected for analysis, namely "Dulu hidup kurasakan mati" [I used to live but felt dead] and "Setelah mati kuhidup semula" [After being dead I am alive again]. This study is a qualitative analysis by applying the inquisitive semantic approach proposed by Nor Hashimah Jalaluddin (2014). The combination of data, theory, philosophy and culture are able to produce meaningful interpretations of the two implicit expressions so as to illustrate the author’s mind. The results of the analysis show that "life" and "death" are not only antonymic at a literal level but have a secondary meaning of dualism. The selection of these two expressions was not done arbitrarily but through the serious thinking of the author. Keywords: figurative language, song lyrics, "Mati hidup Semula", inquisitive semantics